The Relationship of Menstruation Knowledge to Adolescent’s Readiness in Facing Menarche - Chitra Dewi; Ulfa Mutmainnah (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Human body undergoes a variety of changes including growth and development. In Indonesia, average age of menarche was 13 years old, earlier incidence at age less than 9 or 17 years old. This study aimed to relationships of menstruation knowledge to adolescent’s readiness in facing menarche grade VII students at SMPN 5 Pallangga Gowa. This was descriptive analytic with cross sectional study design number of sample was 85 students of 121 population selected by simple random sampling. The results revealed that respondents with lack knowledge and not ready to face menarche were 13 (39.4%), lack knowledge but ready were 20 (60.6%), those with good knowledge but not ready were 10 (19.2%) those who performed good knowledge and ready were 42 (80.8%). It concluded there was a relationship of menstruation knowledge to readiness facing menarche. It encouraged to teachers and parents to provide menarche information and menstruation self-care.